2021
DOI: 10.1002/cncr.33761
|View full text |Cite
|
Sign up to set email alerts
|

Universal social needs assessment in gynecologic oncology: An important step toward more informed and targeted care in the public safety net

Abstract: BACKGROUND: Social needs are actionable mediators of social determinants of health. Along with distress, they affect quality of life and survival in patients with cancer. The objectives of this study were to identify the most common social needs and distress in a largely immigrant gynecologic oncology patient population at a public safety-net hospital and to evaluate for specific needs associated with distress and poor outcomes. METHODS: This was a prospective, survey-based cohort study of patients who partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…By comparison, a similar study performed in Los Angeles among primarily Hispanic patients reported their population needed help reading hospital materials more frequently than needing more social support. 31 However, we feel these differences in findings further highlight the responsibility of health systems to consider not only the needs of gynecologic oncology patients in general, but of assessing and addressing the unique health equity needs of their own specific populations served.…”
Section: Limitationsmentioning
confidence: 92%
“…By comparison, a similar study performed in Los Angeles among primarily Hispanic patients reported their population needed help reading hospital materials more frequently than needing more social support. 31 However, we feel these differences in findings further highlight the responsibility of health systems to consider not only the needs of gynecologic oncology patients in general, but of assessing and addressing the unique health equity needs of their own specific populations served.…”
Section: Limitationsmentioning
confidence: 92%
“…In addition to including essential social need domains—food insecurity, housing instability, utility needs, financial resource strain, and transportation challenges—this survey was adapted to include questions on the optional social need domains of childcare accessibility, health literacy, and social isolation ( Figure ). 15 In addition, patients provided sociodemographic information and breast cancer history.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals with cancer often report at least 1 unmet social need, especially within financial, informational, psychological, and physical domains . However, there is a critical knowledge gap evaluating the impact of unmet social needs on utilization of screening mammography and breast cancer stage at diagnosis, particularly in high-income settings with access to screening mammography …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 61 Social needs screening has been implemented successfully within gynecologic practices and demonstrates a significant opportunity for intervention. 62 , 63 These interventions can be in the form of the Health LEADS model, in which patients are screened, referred to social resources, and followed up to ensure successful resolution of their identified need. 64 …”
Section: Organizationalmentioning
confidence: 99%